Impact of Education and Network for Avian Influenza H5N1 in Human: Knowledge, Clinical Practice, and Motivation on Medical Providers in Vietnam - Manabe, Toshie; Thuy, Pham Thi Phuong; Kudo, Koichiro; Van, Vu Thi Tuong; Takasaki, Jin; Tuan, Nguyen Dang; Co, Dao Xuan; Minh, Dang Hung; Izumi, Shinyu; Binh, Nguyen Gia; Chau, Ngo Quy; Hanh, Tran Thuy (PLOS ONE, 2012)
Background Knowledge, clinical practice, and professional motivation of medical providers relating to H5N1 infection have an important influence on care for H5N1 patients who require early diagnosis and early medical intervention. Methods/Principal Findings Novel educational programs including training and workshops for medical providers relating to H5N1 infection in Vietnam were originally created and implemented in 18 provincial hospitals in northern Vietnam between 2008 and 2010. A self-administered, structured questionnaire survey was conducted in 8 provincial hospitals where both educational training and workshops were previously provided. A total of 326 medical providers, including physicians, nurses, and laboratory technicians who attended or did not attend original programs were enrolled in the survey. Knowledge, clinical attitudes and practice (KAP), including motivation surrounding caring for H5N1 patients, were evaluated. The study indicated a high level of knowledge and motivation in all professional groups, with especially high levels in laboratory technicians. Conferences and educational programs were evaluated to be the main scientific information resources for physicians, along with information from colleagues. The chest radiographs and the initiation of antiviral treatment in the absence of RT-PCR result were identified as gaps in education. Factors possibly influencing professional motivation for caring for H5N1 patients included healthcare profession, the hospital where the respondents worked, age group, attendance at original educational programs and at educational programs which were conducted by international health-related organizations. Conclusions Educational programs provide high knowledge and motivation for medical providers in Vietnam caring for H5N1 patients. Additional educational programs related to chest radiographs and an initiation of treatment in the absence of RT-PCR are needed. Networking is also necessary for sharing updated scientific information and practical experiences. These enhanced KAPs by educational programs and integrated systems among hospitals should result in appropriate care for H5N1 patients and may reduce morbidity and mortality.